Chronic nicotine administration does not alter cognitive or mood associated behavioural parameters. Issue 1 (March 2015) - Ijomone, Omamuyovwi Meashack; Olaibi, Olayemi Kafilat; Mba, Christian; Biose, Ifechukwude Joachim; Tete, Samuel Anthony; Nwoha, Polycarp Umunna
Abstract: Nicotine, the major specific alkaloid in tobacco smoke, exhibits widespread pharmacological effects and may contribute to deterioration in behaviour. The present study thus examined the effects of its chronic administration on some cognitive and mood associated behaviours. Adult rats weighing between 150 and 200 g were randomly divided into 4 groups each of 5 females and 5 males. Three groups were administered graded doses of nicotine at 0.25, 2 and 4 mg/kg body weight via subcutaneous injections. One group served as control and received normal saline (vehicle for nicotine). Behavioural tests were performed using the Y-maze, elevated-plus maze (EPM) and tail suspension tests (TST) at various time points. Nicotine produced no significant effect in spontaneous alternation on Y-maze, nor on six parameters scored on EPM (open arm entries, time spent in open arms, time per open arm entries, open/closed arm quotient, closed arm entries, and total arm entries), and also no significant effect on immobility time in TST. This lack of effects was observed to be independent of sex and dose administered. The study shows that nicotine does not produce long-term changes in some cognitive and mood associated behaviours, thus suggesting it could be well tolerated even following chronic administration.